The effects of nanoclay on the mechanical properties of thermoplastic natural rubber / Nur Laili Hayati Sulaiman - Sulaiman, Nur Laili Hayati (2010)
This paper reports the improvement of a thermoplastic natural rubber (TPNR) composite toughened by the combination of nanoclay. The main objective of this work is to obtaining the quaternary nanocomposite with the mechanical properties such storage modulus, loss modulus and tan delta. The mechanical properties have been evaluated using Dynamic Mechanical Analysis (DMA) on pure TPNR, 3%, 6%, 9% and 12% of nanoclay by different frequency 1Hz and 10Hz. The results show storage modulus increase as the composition of nanoclay increase and as frequency increase because the molecules of bound part are restricted to the surface of the filler, the molecular motion is greatly limited. The loss modulus is decrease as the composition of nanoclay increase and as frequency increase due to the clay has formed an agglomeration of clay inside the matrix. The glass transition (tg) temperature also decrease as the composition of nanoclay increase and as frequency increase because of reduced mobility of the chains due to a strong interaction with the high specific surface nanofiller.